Participação, desigualdades e novas institucionalidades: uma análise a partir de instituições participativas em Santa Catarina - Lígia Helena Hahn Lüchmann; Julian Borba (Ciências Sociais Unisinos)
This work aims to analyze the capacity of inclusion of the poorer sectors of the population in the processes of participative experiences, taking as empirical reference some data on the profile of the representatives and political participants in different spheres of Brazilian political performance (in special, the managing councils of public policies and Participative Budgets - PBs) anchored, more specifically, on the data of cities in Santa Catarina State (south of Brazil). A brief discussion on the political participation is carried on in the beginning, rescuing the main theoretical sources of this debate, followed by a presentation of some empirical data regarding the social economical profile (focusing the data of income and scholar) of the political representatives in the experiences analyzed herein. Finaly, we formulate some possible theoretical explanations for the differences found in the profile of the participants of the managing councils and PBs.